Cruel (im)mobilities and the nearly utopian intimacies of Italian migrants' personal relationships. (1st September 2022) - Humbracht, Michael; Williams, Allan M; Cohen, Scott
Abstract: Most research on visits focuses on (semi)successful connections that equate valued intimacy to adaptation to transnational life and ethno‐national kin obligations. In contrast, we highlight important migrant relationships where adaptation is minimal and contact diminishes, yet they also take on heightened affective intensity. Drawing from a multi‐sited ethnography that includes migrants and friends and family, we examine the affective and ethical dimensions of visits and ICTs (information and communications technology) within the personal relationships of highly skilled Italian migrants in London. Deploying the concepts cruel optimism and polyrhythmia, the paper examines how contrasting rhythms of visits and ICTs provoke reflections and feelings on whether intimacies at a distance are 'real'. Despite difficulties, informants suggest intimacies 'feel normal', imbuing relations with hope for their authenticity that grounds relations in a state of mobile impasse: where feelings of normalcy lead to less interest in recreating connections yet also constructs hope that sustains visits and digital connections.